Variability of omp25 and omp2a Genes in Brucella Strains of Different Taxonomic Position - N. A. Osina; E. G. Boolgakova; A. G. Osin; I. G. Shvidenko; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2024)
The aim of the study was to identify structural differences in the Brucella omp25 and omp2a genes, which make it possible to determine their taxonomic position.Materials and methods. The objects of the study were the nucleotide sequences of the complete genomes of 48 Brucella strains presented in the GenBank NCBI database. To assess sequence homology, the BLAST algorithm and the MEGA 11 program were used.Results and discussion. In 13 species of Brucella and Brucella spp. with unknown species appurtenance, HindIII, EcoRV and EcoRI, AluI restriction profiles of genome regions have been reproduced in silico, including, omp25 and omp2a genes, flanked by primers 25A-25B and 2AB-2AA, respectively. In the omp25 gene, 11 non-synonymous and 24 synonymous mutations have been detected; two deletions: ∆103–108 bp – in В. nosferati, ∆562–597 bp – in В. Ovis; and ACT insertion after 585 bp – in В. vulpis. The variability of the omp2a gene in the studied Brucella strains was significantly higher. 138 SNPs have been identified, of which 60 lead to amino acid substitutions, 2 – form stop codons, and an additional deletion ∆424–561 bp – in В. abortus 1, 2, 4 biovars. Single mutations in the omp2a and omp25 genes had both group specificity – for several species, and unique – for a specific species or biovar of the pathogen. Allelic profiles of the omp25 and omp2a genes have greater resolution than their restriction profiles studied. The identified changes in the structure of the omp25 and omp2a genes correlate with the circulation of individual Brucella species and biovars in the organism of certain carriers. These genes show the presence of deletions, insertions and single polymorphic nucleotides specific to species, groups of species and, in some cases, biovars of the pathogen.